CUSTOMER SATISFACTION ANALYSIS WITH SERVICE QUALITY METHOD AT ALDO PHOTOGRAPHY BENGKULU CITY - Syaputra, Rivaldo Yogi; Syofian, Syofian; Hidayati, Arifah (STMIK Pringsewu, 2024)
Service is one of the factors that determine customer satisfaction. customer satisfaction. Servqual which is the basis for measuring service quality consists of of Tangible, Realibility, responsiveness, Assurance and Empathy. This study aims to determine the effect of Tangible, Realibility, Responsiveness, Assurance and Empathy on Aldo customer satisfaction. Photography partially and simultaneously.This research is quantitative research associative research, with the population being Aldo Photography customers. The number of research samples is 170 samples where the sample determination uses purposive sampling method with sample criteria are Aldo Photography customers starting from 2020-2024. The type of data used is survey data by distributing questionnaires to respondents using Google form and analyzed using multiple linear regression analysis and multiple correlation. analysis and multiple correlation. The research results are 1) Tangibility has a significant influence on customer satisfaction of Aldo Photography Bengkulu City; 2) Reliability has a significant influence on customer satisfaction customer satisfaction of Aldo Photography Bengkulu City Bengkulu; 3) Responsiveness has a significant influence on customer satisfaction Aldo Photography Bengkulu City; 4) Assurance has a significant influence on customer satisfaction Aldo Photography Bengkulu City; 5) Empathy has a significant effect on customer satisfaction of Aldo Photography Bengkulu City; and 6) Tangibles, reliability, responsiveness, assurance and empathy simultaneously have a significant effect on customer satisfaction of Aldo Photography Bengkulu City. Bengkulu City.